1996
DOI: 10.1177/001088049603700117
|View full text |Cite
|
Sign up to set email alerts
|

Restaurant Marketing on the Worldwide Web

Abstract: A large portion of the so-called information superhighway is the internet, which allows people to communicate through computers using electronic mail, bulletin boards, and news groups, among other means. One section of the internet, the worldwide web (WWW), is a network of computers carrying information for public dissemination. Many companies, institutions, and individuals have created WWW "home pages," which are computer files with text, graphics, and links to other, related pages. "Visitors" to web pages ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…Also important is the quality of the websites, as has been shown by various studies applied to firms in the tourism sector (Noone & Mattila, 2009;Rong et al, 2009). While it seems clear that a restaurant's website design has a direct impact on its customers' expectations and satisfaction (Wang, Cheng, & Huang, 2004), few studies have analyzed restaurants' use of the Web as a marketing tool (Gregory, Wang, & DiPietro, 2010;Murphy, Forrest, & Wotring, 1996). Hwang, Yoon, and Park, (2011) note that there have been very few studies analyzing the Internet marketing applied to the restaurant sector and far between despite the potential importance of their findings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also important is the quality of the websites, as has been shown by various studies applied to firms in the tourism sector (Noone & Mattila, 2009;Rong et al, 2009). While it seems clear that a restaurant's website design has a direct impact on its customers' expectations and satisfaction (Wang, Cheng, & Huang, 2004), few studies have analyzed restaurants' use of the Web as a marketing tool (Gregory, Wang, & DiPietro, 2010;Murphy, Forrest, & Wotring, 1996). Hwang, Yoon, and Park, (2011) note that there have been very few studies analyzing the Internet marketing applied to the restaurant sector and far between despite the potential importance of their findings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This leads their public relations efforts and accomplishes the marketing [29]. Such efforts through the restaurants' Web sites encourage customers to visit the Web sites and ultimately strengthen the competitive power of family restaurants [19][26] [47]. This study will analyze various relationships among family restaurant Web site strategies, such as the customers' intention to use, actual use, satisfaction, and their recommendations to others to use these Web sites.…”
Section: Family Restaurant Web-site Strategymentioning
confidence: 99%
“…Many companies that operate family restaurants but have not focused on using the Internet to enhance customer service in the past are now creating efforts to make their various services available to customers online [26] [29]. The presentation of online services strengthens the strategy of family restaurants by allowing them to provide a variety of information through their Web sites and offer various kinds of gifts, special events, discount coupons, or other items that will promote the customers' interest in visiting family restaurants [19]. The use of family restaurants' Web sites as a marketing strategy will ultimately be shown to improve both customer satisfaction and create better results for management goals.…”
Section: Introductionmentioning
confidence: 99%
“…In this new world of the Internet, a website provides a restaurant with a new and more direct means of communicating with its customer base (Murphy, Forrest & Wotring, 1996).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In their study Murphy, et al (1996) evaluated 37 websites and concluded that with proper implementation, websites could be a powerful tool to communicate with customers in a more personal fashion versus a commercial on television. However, in order to communicate with the customer, the restaurant must first get them to the site and then keep them there (Hutchcraft, 2000).…”
Section: Literature Reviewmentioning
confidence: 99%